A Field of Green: Renewable Energy Research on the Web. - Dawn Lowe-Wincentsen (Issues in Science and Technology Librarianship)
The article provides information about web sites that provide resources for research on renewable energy. For news feeds, the websites include Alternative Energy at www.alternative-energy-news.info/, Green Inc. at http://greeninc.blogs.nytimes.com/, and EcoSeed at www.ecoseed.org/. For databases, the websites are Association of Energy Engineers at http://aeecenter.metapress.com/app/home/main.asp, Database for State Incentives for Renewables and Efficiency (DSIRE) at www.dsireusa.org/, and Energy Citations Database at www.osti.gov/energycitations/.